Colony contact contributes to the diversity of gut bacteria in bumblebees (Bombus terrestris). (15th February 2016) - Billiet, Annelies; Meeus, Ivan; Van Nieuwerburgh, Filip; Deforce, Dieter; Wäckers, Felix; Smagghe, Guy
Abstract: Social bees, like honeybees and bumblebees, have a close contact with nest mates of different developmental stages and generations. This could enhance bacterial transfer between nest mates and offers opportunities for direct transfer of symbionts from one generation to the next, resulting in a stable host specific gut microbiota. Gut symbionts of honeybees and bumblebees have been suggested to contribute in digestion and protection against parasites and pathogens. Here we studied the impact of contact with the bumblebee colony on the colonization potential of the bacterial families (i.e., Neisseriaceae, Orbaceae, Lactobacillaceae and Bifidobacteriaceae ) occurring in the gut of adult bumblebees ( Bombus terrestris ). Bacterial profiles of the gut microbiota of B. terrestris were determined based on the hypervariable V4 region of the 16S rRNA using paired‐end Illumina sequencing. In our experiments, we created different groups in which we gradually reduced the contact with nest mates and hive material. We made 3 observations: (i) reducing the contact between the colony and the bumblebee during adult life resulted in a significant drop in the relative abundance of Lactobacillus bombicola and Lactobacillus bombi ; (ii) Bifidobacteriaceae required contact with nest mates to colonize the gut of B. terrestris and a significant lower bacterial diversity was observed in bumblebees that were completely excluded from colony contact during the adult life; (iii) Snodgrassella and Gilliamella were able to colonize the gut of the adult bumblebee without any direct contact with nest mates in the adult life stage. These results indicate the impact of the colony life on the diversity of the characteristic bumblebee gut bacteria.